2017
DOI: 10.5194/angeo-35-763-2017
|View full text |Cite
|
Sign up to set email alerts
|

Features of 3–7-day planetary-wave-type oscillations in F-layer vertical drift and equatorial spread F observed over two low-latitude stations in China

Abstract: Abstract. Recent studies on the equatorial atmosphere–ionosphere coupling system have shown that planetary-wave-type oscillations, as an important seeding mechanism for equatorial spread F (ESF), play an important role in ESF irregularity development and its day-to-day variability in the equatorial latitudes. In this study, ionosonde virtual height and ESF measurements over Sanya (18.4° N, 109.6° E; 12.8° N dip latitude) and meteor radar neutral-wind measurements over Fuke (19.5° N, 109.1° E; 14° N dip latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Unlike the fast Fourier transform (FFT), it can be used even when the data has gaps and the sampling is aperiodic. LS technique of frequency transformation is used effectively in the geo‐scientific applications to derive dominant time periods even if the time series is shorter than the periodicities of interest [Zhu et al, ]. Frequency resolution of LS technique is better than the FFT and is utilized in the applications where exact time period is required to be extracted from a time series not significantly longer than the period of interest.…”
Section: Results During 2015 (High‐moderate Solar Flux)mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the fast Fourier transform (FFT), it can be used even when the data has gaps and the sampling is aperiodic. LS technique of frequency transformation is used effectively in the geo‐scientific applications to derive dominant time periods even if the time series is shorter than the periodicities of interest [Zhu et al, ]. Frequency resolution of LS technique is better than the FFT and is utilized in the applications where exact time period is required to be extracted from a time series not significantly longer than the period of interest.…”
Section: Results During 2015 (High‐moderate Solar Flux)mentioning
confidence: 99%
“…Planetary waves, like Kelvin waves, propagate to mesospheric heights and above, modifying the dynamically controlled component of the E region conductivity in form of the Es density, which in turn influences the F region dynamo and RT instability growth rate (Abdu and Brum, 2009). Recently, Zhu et al (2017) proposed a similar mechanism for planetary wave effects. While most of the investigations have so far highlighted 3-to 7-day wave activity in the ionospheric irregularities, longer periodicities have mostly been reported in the background ionospheric parameters.…”
Section: 1029/2018ja026419mentioning
confidence: 99%
See 1 more Smart Citation
“…On 27 March 2014 (DOY86), CTR was very large (CTR = 16.6) and ASY was small (ASY = 0.034), scintillation was also absent. These imply that there would be other key factors controlling the occurrence of post-sunset irregularities and scintillation, besides zonal electric field and neutral wind, such as gravity waves (e.g., Aswathy & Manju, 2017), planetary waves (e.g., Manju & Aswathy, 2020;Zhu et al, 2017) or wave-like structures (Li et al, 2012;Narayanan et al, 2012). As Li et al (2012) and Narayanan et al (2012) indicated that the presence of Large-Scale Wave Structure (LSWS) alone was not sufficient to initiate the development of R-T instability, and the strong zonal electric field (E × B) alone may also not sufficient to trigger the occurrence of irregularities, both the strong zonal electric field and meridional wind cannot trigger the occurrence of irregular ities and scintillation under the absent of seed perturbation or wave-like structures.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, observations have shown that there is a strong day-to-day variability of the EPB occurrence and development (e.g., Carter et al, 2014;Abdu, 2019) and it is a topic of current research. There is evidence of planetary waves acting in the neutral 10 winds and consequently changing the background condition of the atmosphere (e.g., Forbes, 1996;Takahashi et al, 2006;Abdu and Brum, 2009;Chang et al, 2010;Zhu et al, 2017). Stening and Fejer (2001) published the first work proposing the influence of lunar tides in the probability of occurrence of EPBs.…”
mentioning
confidence: 99%